Penggunaan Pow Tree dalam Pengajaran Writing Pada Jurusan Pendidikan Bahasa Inggris di Universitas Madura - Yulliarsih Yuliarsih; Evha Nazalatus Sa'adiyaSy (Universitas Islam Madura, 2019)
Abstract: The researcher raises two questions of research, they are: (1) how does the Writing lecturer implement Pow-Tree strategy in teaching writing subject at English department in Madura University, (2) how does students' progress in writing. This research is descriptive qualitative research. There are three research instruments are used to collect the data needed, they are: observation, interview, and, documents. The subject of this research are 11 students of four semester at English Department in Madura University. Based on the research analysis result in implementing strategy of Pow-Tree in three phases of teaching writing. This strategy was implemented in the second phase-whilst phase. There are seven steps in implementing this strategy in the writing subject. The lecturer was demanded to use real example that related with the students’ daily life experienced. This strategy was success in gaining students interest in writing paragraph. The students as the subject of this research said that this helped them to organize their paragraph writing compose. Keywords: Pow-tree Strategy, Student Interest, Writing Abstrak: Penelitian bertujuan untuk menjawab dua pertanyaan, yaitu (1) bagaimana penerapan strategi Pow-Tree pada mata kuliah Menulis pada jurusan Pendidikan Bahas Inggris yang dilakukan oleh dosen di Universitas Madura (2) bagaimana kemajuan siswa dalam menulis. Untuk menjawab pertanyaan ini peneliti menggunakan pendekatan deskriptif dengan jenis penelitian kualitatif. Ada tiga jenis instrument yang digunakan untuk memperoleh data, yaitu: observasi, wawancara, dokumen. Penelitian ini menggunakan 11 orang mahasiswa semester empat pendikan Bahasa Inggris di Universitas Madura. Setelah menganalisis data dimana penerapan strategi Pow-Tree digunakan dalam tiga tahapan pembelajaran. Strategi ini diterapkan pada tahapan inti pembelajaran dengan menggunakan tujuh langkah pembelajaran. Dosen menerapkan strategi ini dengan menggunakan contoh yang berkaitan langsung dengan kehidupan sehari-hari yang dihadapi oleh mahasiswa. Dengan strategi ini mahasiswa lebih bisa focus dalam penggorganisasian karangan dalam bentuk paragraph.